Case-Based Blended Learning in Catholic Education: Enhancing Critical Thinking toward SDG 4 and SDG 10 in Eastern Indonesia - Evaristus Silitubun; Mustaji Mustaji; Dewi Utari (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to examine the effectiveness of the Case Based Blended Learning (CB2L) model in improving the critical thinking skills of grade X students in Catholic Religious Education at a senior high school in Jayapura, Papua. This article reports the summative quasi-experimental phase of a broader research and development (R&D) project. Method: The study employed a quasi-experimental design using a non-equivalent control group pretest-posttest design involving 60 grade X students. The experimental class was taught using the CB2L model, while the control class received conventional instruction. The CB2L model consisted of seven learning phases: case determination, self learning, group formation, case analysis, discovery information, presentation, and evaluation. Data were collected through a case-based essay test measuring critical thinking skills and analyzed using descriptive statistics, independent samples t-test, normalized gain (N-gain), and effect size estimation. Results: The experimental group achieved a higher posttest score (M = 82.97, SD = 5.31) than the control group (M = 69.67, SD = 7.25). The difference was statistically significant, t = 8.107, p < .001, with a mean difference of 13.30 points. The experimental group also demonstrated a moderate normalized gain (N-gain = 0.421), with mean scores increasing from 58.42 to 81.37. These findings indicate that the CB2L model effectively strengthens students’ critical thinking through the integration of authentic moral cases, individual online preparation, collaborative case analysis, information discovery, presentation, and guided reflection. The novelty of this study lies in the implementation of an integrated Case Based Blended Learning model in Catholic Religious Education, combining authentic case-based learning with blended learning to foster critical thinking within a faith-based educational context. The study also provides empirical evidence from a geographically and culturally distinctive setting in Papua, demonstrating that contextual, technology-supported, and value-based learning can effectively enhance higher-order thinking skills in religious education.